2020
DOI: 10.1177/2050640620943089
|View full text |Cite
|
Sign up to set email alerts
|

The new simplified MARIA score applies beyond clinical trials: A suitable clinical practice tool for Crohn’s disease that parallels a simple endoscopic index and fecal calprotectin

Abstract: Background A simplified magnetic resonance enterography (MRe) index (sMARIA) for Crohn’s disease (CD) was recently developed and validated. Objective Our aims were (a) to assess sMARIA’s accuracy in a sample other than the validation cohort; (b) to evaluate its correlation with a simpler endoscopy index (SES-CD) and fecal calprotectin (FC); and (c) to assess the need of an expert radiologist to reliably use sMARIA. Methods Patients with CD who underwent MRe, ileocolonoscopy and FC within 2–4 weeks had their MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…23 Yet, the reference standard for evaluating MRE indices for CD severity assessment remains endoscopic scores such as the SES-CD. 24 However, current MRE indices achieved only a moderate correlation with the reference endoscopic scores. In this study, we hypothesized that the moderate correlation to the TI SES-CD achieved by MRE indices may be attributed, at least in part, to the utilization of classical linear regression models to characterize the correlation between the MRE-based variables and EH which limited their ability to determine the potentially complex, non-linear correlation.…”
Section: Discussionmentioning
confidence: 93%
“…23 Yet, the reference standard for evaluating MRE indices for CD severity assessment remains endoscopic scores such as the SES-CD. 24 However, current MRE indices achieved only a moderate correlation with the reference endoscopic scores. In this study, we hypothesized that the moderate correlation to the TI SES-CD achieved by MRE indices may be attributed, at least in part, to the utilization of classical linear regression models to characterize the correlation between the MRE-based variables and EH which limited their ability to determine the potentially complex, non-linear correlation.…”
Section: Discussionmentioning
confidence: 93%
“… 14 Roseira and colleagues evaluated the sMARIA index in a series of 84 patients. 25 For identifying active disease, they reported that the per-segment diagnostic accuracy of sMARIA had a sensitivity and specificity of 90% and 98%, respectively. Similarly, Tao et al found the sMARIA score provided a sensitivity of 81.4% and 88.9%, and a specificity of 90.8% and 95.1%, for identifying active and severe CD, respectively, with a Simple Endoscopic Score for Crohn’s Disease [SES-CD] reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…The sMaRIA has also been validated against endoscopic standards of reference (Crohn's disease endoscopic index of activity [CDEIS] and the simple endoscopic score for Crohn's disease (SES-CD)). [47][48][49] The London and 'extended' scores were derived and validated using a histological standard of reference 50 and were subsequently validated against the CDEIS. 51 The components of the sMaRIA and extended London score are very similar; however, whereas the sMaRIA and London scores can be applied regardless of whether contrast material administration, the extended London score cannot.…”
Section: Recent Advances In Clinical Practicementioning
confidence: 99%
“…These drawbacks led to the development of the simplified MaRIA (sMaRIA), which requires much less time to calculate, and normal segments do not account in the global score. The sMaRIA has also been validated against endoscopic standards of reference (Crohn's disease endoscopic index of activity [CDEIS] and the simple endoscopic score for Crohn's disease (SES-CD)) 47–49…”
Section: Introductionmentioning
confidence: 99%